2022
DOI: 10.3390/ani13010065
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Characterization of Feline Calicivirus Associated with Paw and Mouth Disease

Abstract: Feline calicivirus (FCV) infection in cats can led to several diverse clinical presentations, ranging from mild upper respiratory signs to virulent systemic disease. Herein, we report a paw and mouth disease case in a 7-year-old household cat due to an FCV infection. An asymptomatic cat living in the same household was also infected with FCV. Clinical and pathological investigations were combined with the molecular and phenotypical characterization of the FCV strains. The RNA of the FCV was detected using qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 52 publications
1
3
0
Order By: Relevance
“…Forty-six percent of patients with limb edema had edema in all four legs, but no trend toward a specific leg was found. In some patients with limb edema, progression to skin lesions, such as erosions, ulcers, or crusts, was observed, which was similar to the progression observed in a previous study [ 4 ]. However, unlike in the previous study, lesions on footpads were not clearly observed in the patients in the present study.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Forty-six percent of patients with limb edema had edema in all four legs, but no trend toward a specific leg was found. In some patients with limb edema, progression to skin lesions, such as erosions, ulcers, or crusts, was observed, which was similar to the progression observed in a previous study [ 4 ]. However, unlike in the previous study, lesions on footpads were not clearly observed in the patients in the present study.…”
Section: Discussionsupporting
confidence: 87%
“…Lymphopenia is observed in several viral infections, including FCV-VSD, and is associated with disease severity, although the exact mechanism is unknown [ 4 26 ]. In previous studies, lymphopenia, neutrophilia, and thrombocytopenia were observed on CBC in some cats with FCV-VSD [ 8 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Feline calicivirus (FCV) is considered one of the major pathogens that infects cats worldwide [1][2][3]. The virus causes an upper respiratory tract disease with typical clinical symptoms such as acute respiratory disease and oral ulceration [1][2][3][4][5][6][7][8][9][10][11]. The small number of cats infected by a highly virulent strain of FCV (vs.-FCV) suffer severe and fatal systemic disease symptoms, including subcutaneous oedema, multiple necrosis events, severe pneumonia, feline chronic gingivostomatitis and acute arthritis and limping [10,12,13].…”
Section: Introductionmentioning
confidence: 99%